IMPLEMENTATION OF THE MABAC–ENTROPY ALGORITHM FOR TOURIST DESTINATION RECOMMENDATIONS - Fauzan Ramadhani (Infotronik : Jurnal Teknologi Informasi dan Elektronika, 2026)
Tourism in West Java continues to grow with the increasing number of destinations and visitor interest. This situation creates challenges in selecting tourist attractions due to the abundance of alternatives and limited information regarding ticket prices, distance, facilities, security, and destination ratings. This study aims to develop a decision support system by implementing the Multi-Attributive Border Approximation Area Comparison (MABAC) method for alternative ranking and the Entropy method for criteria weighting. The research data were collected from 20 tourist attractions in West Java, with 10 destinations selected as samples and analyzed using predetermined criteria. The developed recommendation system is capable of processing various criteria such as ticket price, distance, facilities, security, and ratings, resulting in a more objective ranking of destinations. The ranking process produced an ordered list of destinations with different preference values, where Taman Bunga Nusantara ranked first with a score of 0.294, followed by the Bogor Botanical Garden with 0.178, and Farm House Susu Lembang with 0.166. These results demonstrate that the combination of the MABAC and Entropy methods can provide objective and systematic recommendations for tourist destinations. Therefore, the developed system is expected to assist users in making tourism choices more quickly and efficiently.